Migration and development, without care? Locating transnational care practices in the migration‐development debate. Issue 3 (30th January 2023) - Withers, Matt; Hill, Elizabeth
Abstract: Highly‐restrictive temporary labour migration schemes are commonplace throughout the Indo‐Pacific region and continue to expand amid sustained policy enthusiasm for 'migration‐development'. Yet, the developmental benefits of guestworker schemes are routinely evaluated according to narrow economic criteria, with little consideration given to transnational family separation and the displacement of socially reproductive labour that sustains everyday life. 'Migration', 'development' and 'care' are deeply interlinked political economic processes, yet they have been theorised in partial isolation. We challenge this analytical disconnect, situating the developmental implications of guestworker migration in relation to the total social organisation of labour, and argue for a more holistic 'migration‐care‐development' nexus that foregrounds unsustainable disruptions to care economies. We ground our framework in the context of Australia's Pacific Labour Scheme to illustrate the developmental consequences for Pasifika households and communities, highlighting the need for 'decent care' policies to address care deficits in support of sustainable and gender‐equitable development.